The reliability and utility of spirometry performed on people with asthma in community pharmacies - Lei Burton, D.; LeMay, K.; Saini, B.; Smith, L.; Bosnic-Anticevich, S.; Southwell, P.; Cooke, J.; Emmerton, Lynne; Stewart, K.; Krass, I.; Reddel, H.; Armour, C. (Taylor and Francis Ltd, 2015)
Objective: To investigate the reliability and the utility of spirometry generated by community pharmacists participating in two large asthma intervention trials of 892 people. Methods: The Pharmacy Asthma Care Program (PACP) and the Pharmacy Asthma Management Service (PAMS) involved up to four visits to the pharmacy over 6 months for counseling and goal setting. Pharmacists performed spirometry according to ATS/ERS guidelines to inform management. The proportion of A–E, F quality tests, as per EasyOne™ QC grades, were recorded. Lung function results between visits and for participants referred/not referred to their general practitioner on the basis of spirometry were compared. Results: Complete data from 2593 spirometry sessions were recorded, 68.5% of spirometry sessions achieved three acceptable tests with between-test repeatability of 150 ml or less (A or B quality), 96% of spirometry sessions included at least one test that met ATS/ERS acceptability criteria. About 39.1% of participants had FEV1/FVC values below the lower limit of normal (LNN), indicating a respiratory obstruction. As a result of the service, there was a significant increase in FEV1 and FEV1/FVC and asthma control. Lung function values were significantly poorer for participants referred to their general practitioner, compared with those not referred, on the basis of spirometry. Conclusions: Community pharmacists are able to reliably achieve spirometry results meeting ATS/ERS guidelines in people with asthma. Significant improvements in airway obstruction were demonstrated with the pharmacy services. Pharmacists interpreted lung function results to identify airway obstruction for referral, making this a useful technique for review of people with asthma in the community.